Two-dimensional semiconductor transition metal dichalcogenide nanosheets as charge carriers in metallophthalocyanine based solar cells - Nombona, Nolwazi (University of Pretoria, 2020)
Dissertation (MSc (Chemistry))--University of Pretoria, 2020.